Alternatives to intention-to-treat analyses - Geldsetzer, Pascal; Bärnighausen, Till; Sudharsanan, Nikkil (The journal of the American Medical Association, 2019)
To the Editor Drs DeMets and Cook discussed the intention-to-treat (ITT) principle, which is generally the most assumption-free method for analysis of randomize